Eosinophilic Esophagitis: An Emerging Disease in Childhood – Review of Diagnostic and Management Strategies - Papadopoulou, Alexandra; Dias, Jorge Amil (Frontiers in Pediatrics, 2014)
Eosinophilic esophagitis (EoE) is a chronic immune/antigen mediated inflammatory disease of the esophagus. It comprises a separate entity of increasing incidence and prevalence in children and adults. The disease is characterized by histological evidence of dense esophageal tissue eosinophilia in the presence of a variety of upper GI symptoms including vomiting, dysphagia, food impaction and odynophagia. Cornerstone of treatment is dietary intervention and/or the off-label use of swallowed topical corticosteroids. New drug therapies are under investigation. In this review we focus on the diagnostic approach and the currently available treatment strategies. Keywords: Eosinophilic esophagitis, oral viscous budesonide, fluticasone propionate, oral steroids, amino acid-based formula, empiric elimination diet, targeted elimination diet Key points: 1. A trial with antisecretory medication is necessary to exclude GERD and PPI-responsive esophageal eosinophilia and to fulfil the diagnostic criteria of EoE. 2. Elimination diet and/or off-label use of topical corticosteroids are effective measures for treating EoE. 3. Elimination diet is the first line treatment in atopic children. 4. Systemic corticosteroids are reserved for patients with severe disease requiring immediate relief, or when other treatments have failed. 5. Cromolyn sodium (sodium cromoglycate) and leukotriene receptor antagonists, are not currently recommended for treating EoE, due to lack of solid evidence of benefit. 6. Immunosuppressive drugs and biologics have shown some value but effect has been limited and therefore not yet recommended as standard therapy.